Metacognition in wild Japanese macaques: cost and stakes influencing information-seeking behavior - Lorraine Subias; Noriko Katsu; Kazunori Yamada (Animal Cognition)
Abstract Metacognition allows us to evaluate memories and knowledge, thus enabling us to distinguish between what we know and what we do not. Studies have shown that species other than humans may possess similar abilities. However, the number of species tested was limited. Testing ten free-ranging Japanese macaques (Macaca fuscata) on a task in which they had to find food hidden inside one of the four opaque tubes, we investigated whether these subjects would seek information when needed. The monkeys could look inside the tubes before selecting one. We varied three parameters: the baiting process, the cost that monkeys had to pay to look inside the tubes, and the reward at stake. We assessed whether and how these parameters would affect the monkeys’ tendency to look inside the tube before selecting one. When they were not shown which tube contained the reward, nine monkeys looked significantly more frequently in at least one condition. Half of them tended to reduce their looks when the cost was high, but only when they already knew the location of the reward. When a high-quality reward was at stake, four monkeys tended to look more inside the tubes, even though they already knew the reward’s location. Our results are consistent with those of rhesus macaques, suggesting that metacognitive-like abilities may be shared by Cercopithecidae, and that, at least some monkeys may be aware of their lack of knowledge.